Evaluation of anaesthesia methods in caesarean section for foetal distress - Wahjoeningsih, Sri; Witjaksono, Widowati (Universiti Sains Malaysia, 2007)
The purpose of this study was to evaluate the anaesthetic technique for Caesarean section which was appropriate for the clinical situation. This retrospective study was conducted on 240 patients undergoing Caesarean section with indications of foetal distress during 3 years period (2002-2004). The data were reviewed from the patients medical record of the Department of Anesthesiology, Dr Soetomo Hospital, Surabaya. The patients were divided into three groups according to the criteria of foetal heart rates. The success of the anaesthesia methods was determined by assessing the Apgar scores of the newborn baby. The results were analyse using Kruskal-Wallis, Chi-Square. P <0.05 was considered as statistically significant. 1- and 5-minute Apgar score of the normal range group was significantly higher than that of the bradycardia group (p<0.05), but no significant differences was found between the normal range and the tachycardia group (p>0.05). One-and five-minute Apgar scores of the sub-arachnoid block group were significantly higher than those of the general anesthesia group (p<0.05). One minute Apgar score of the ketamine group was significantly higher than that of the thiopental group (p<0.05), but no significant differences in 5-minute Apgar score was found between the ketamine and the thiopental groups ( p>0.05). We conclude that subarachnoid block is the choice of anaesthesia for the patients underwent Caesarlan section with foetal distress's diagnose at PS 1 and 2 patients. General anaesthesia with ketamine Apgar score at one minute better than that of,the thiopental.